Analisis Keamanan Informasi Menggunakan Tools Indeks Kami ISO 4.1 - Ade Kornelia; Dedi Irawan (Jurnal Pengembangan Sistem Informasi dan Informatika, 2021)
Information is a very valuable asset for a university institution. Utilization of information technology offers various conveniences in obtaining the information needed. Good information management can make universities have good managerial skills. protecting information security means that it also requires efforts to pay attention to the security factors of all supporting assets such as networks, as well as other facilities that are directly or indirectly related to the process of organizing information. Bina Darma University is an institution that is engaged in the field of education and science, which has a vision that is to become an International Standard University Based on Information Technology By 2025, to realize this there are several efforts prepared, one of which is to improve information security by implementing the ISO 27001 certification process. :2013. So in the context of Bina Darma University will implement ISO 27001: 2013. Using the method of Applied Research (applied research) the author took the initiative to conduct research with the title ANALYSIS OF INFORMATION SECURITY USING OUR INDEX TOOLS 4.1 So as to produce Knowing the maturity level of information security with a status of Inappropriate, Needs improvement , Enough and Good at Bina Darma University.